Bacterimetria e colimetria em bebidas refrigerantes consumidas em Santa Maria, RS - Brum, Marco Antonio R. de; Terra, Nelcindo N.; Froeming, Beatriz; Durand, Cleci Centeno (Revista do Centro de Ciências Rurais, 2008)
Os autores realizaram bacterimetria e colimetria de bebidas refrigerantes, consumidas em Santa Maria, RS, constatando contagens reduzidas para flora total viável e colimetria negativa. Abstract The autors made colimetry and bacterimetry of soft drinks, drinked at Santa Maria, RS. They discovered very low amounts of viable total flora and the colimetry was also negative.